Platelet-promoting drug delivery efficiency for inhibition of tumor growth, metastasis, and recurrence - Li, Xiaoliang; Hu, Lanyue; Tan, Chengning; Wang, Xiaojie; Ran, Qian; Chen, Li; Li, Zhongjun (Frontiers in Oncology, 2022)
Nanomedicines are considered one of the promising strategies for anticancer therapy; however, the low targeting efficiency of nanomedicines in vivo is a great obstacle to their clinical applications. Camouflaging nanomedicines with either platelet membrane (PM) or platelet would significantly prolong the retention time of nanomedicines in the bloodstream, enhance the targeting ability of nanomedicines to tumor cells, and reduce the off-target effect of nanomedicines in major organs during the anticancer treatment. In the current review, the advantages of using PM or platelet as smart carriers for delivering nanomedicines to inhibit tumor growth, metastasis, and recurrence were summarized. The opportunities and challenges of this camouflaging strategy for anticancer treatment were also discussed.